2010
DOI: 10.1111/j.1365-3083.2010.02471.x
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Interfering RNA‐Mediated Identification and Regulation of the Ternary SNARE Complex Mediating RBL‐2H3 Mast Cell Degranulation

Abstract: Dysregulation of mast cell function contributes to allergic and autoimmune disease that affects more than 70 million persons in the United States alone. Identifying novel mast cell targets that mediate disease or disease progression is required for the development of innovative therapeutics for the treatment of allergy/asthma and autoimmune disease. RNA interference technologies offer hope both as basic research tools for target identification and as potential, novel, specific therapeutics. Soluble N‐ethylmale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…The SNAP-25 family consists of multiple isoforms, including SNAP-25a, SNAP-25b, and SNAP-23. It is noteworthy in this regard that a recent study reported that the specific SNAP-25a/b antibody used here did not detect the abundant SNAP-23 in mast cells (Woska and Gillespie 2011). This finding demonstrates that this antibody exhibits no or very weak cross-reactivity with SNAP-23 and argues that the ''SNAP-25'' detected in our experiments was a composite of the neuron-specific SNAP-25a and SNAP25b isoforms only.…”
Section: Discussionmentioning
confidence: 67%
“…The SNAP-25 family consists of multiple isoforms, including SNAP-25a, SNAP-25b, and SNAP-23. It is noteworthy in this regard that a recent study reported that the specific SNAP-25a/b antibody used here did not detect the abundant SNAP-23 in mast cells (Woska and Gillespie 2011). This finding demonstrates that this antibody exhibits no or very weak cross-reactivity with SNAP-23 and argues that the ''SNAP-25'' detected in our experiments was a composite of the neuron-specific SNAP-25a and SNAP25b isoforms only.…”
Section: Discussionmentioning
confidence: 67%
“…VAMP8 can control various stages of granule-mediated secretion. Mast cells undergo piecemeal degranulation, which is regulated through the VAMP8 and VAMP7 as R-SNAREs located on secretory granules and Stx4/SNAP23 on the cell surface [92,96,[98][99][100]. In pancreatic acinar cells VAMP8 regulates granule-to-granule, but not granule-to-surface, fusion during compound exocytosis, whether this is the case for mast cell is unclear [101].…”
Section: Tnf Secretion From Mast Cellsmentioning
confidence: 97%
“…The ability of RNAi to inhibit virulent gene expression has been widely used to treat a variety of diseases (33)(34)(35). Also, a number of studies have reported that RNAi can be used in DCs to diagnose and treat bronchial asthma (36)(37)(38)(39). Darcan-Nicolaisen et al (40) discovered that the two major signs of allergic asthma in the OVA-induced asthma mouse model, which are airway inflammation and hyperactivity, were significantly ameliorated by signal transducer and activator of transcription 6 (STAT6) silencing in airway epithelial cells using the administration of siRNA nose drops.…”
Section: Discussionmentioning
confidence: 99%